IMPLEMENTASI CRM PADA TOKO INDAH VINO JAYA BERBASIS WEB - Anggita Purwandari; Juna Eska; Febby Madonna Yuma (LPPM STMIK Royal Kisaran, 2022)
Abstract :Toko Indah Vino Jaya is a business that operates in the field of selling women's fashion. Currently, the marketing system and business activities carried out by Toko Indah Vino Jaya are still manual and conventional. So for this reason there needs to be improvements to the sales system by implementing technology in it in the form of implementing CRM E-Marketing in the form of a website. By implementing Customer Relationship Management, companies can find out what is needed and expected from their customers which will then be able to create good business relationships. With E-Marketig technology in the form of a website, the aim is to support marketing so that customer reach will be wider and can help speed up performance at the Dilla Collection. The system design was built using the PHP programming language and MySQL database. The results of this research show that the information system design that has been built can make it easier for consumers to get information about products and make it easier for companies to introduce the products they offer.Keywords : customer relationship management; e-marketing; MySQL; PHP Abstrak : Toko Indah Vino Jaya bergerak dibidang penjualan fashion wanita. Sekarang ini sistem pemasaran dan kegiatan usaha yang dilakukan oleh Toko Indah Vino Jaya masih secara manual dan konvensional. Maka untuk itu perlu ada perbaikan pada sistem penjualannya dengan cara menerapkan teknologi didalamnya berupa penerapan CRM E-Marketing dalam bentuk wabsite. Dengan menerapkan Customer Relationship Manajemen perusahaan dapat mengetahui apa yang diperlukan dan yang diharapkan dari pelanggannya yang nantinya mampu meciptakan hubungan bisnis yang baik. Dengan adanya teknologi E-Marketig dalam bentuk website betujuan untuk menunjang pemasaran sehingga jangkauan pelangan akan lebih luas lagi serta dapat membantu mempercepat kinerja pada Dilla Collection. Perancangan sistem yang dibangun menggunakan bahasa pemograman PHP dan database MySQL. Hasil dari penelitian ini bahwa rancangan sistem informasi yang telah dibangun dapat memudahkan konsumen mendapatkan informasi tentang produk serta mempermudah perusahaan dalam memperkenal produk-produk yang mereka tawarkan.Kata kunci : customer relationship management; e-marketing; MySQL; PHP